2015
DOI: 10.48550/arxiv.1511.04707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Linear Discriminant Analysis

Abstract: We introduce Deep Linear Discriminant Analysis (DeepLDA) which learns linearly separable latent representations in an end-to-end fashion. Classic LDA extracts features which preserve class separability and is used for dimensionality reduction for many classification problems. The central idea of this paper is to put LDA on top of a deep neural network. This can be seen as a non-linear extension of classic LDA. Instead of maximizing the likelihood of target labels for individual samples, we propose an objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 13 publications
0
39
1
Order By: Relevance
“…To make a comparison with DLDA, the same network architecture and parameters in Dorfer et al (2015) were used in the following experiments. The network architecture renamed as DorferNet is depicted in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To make a comparison with DLDA, the same network architecture and parameters in Dorfer et al (2015) were used in the following experiments. The network architecture renamed as DorferNet is depicted in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…By focusing on directions in the latent space with smallest discriminative power, DLDA learns linearly separable hidden representations with similar discriminative power in all directions of the latent space. Although Dorfer et al (2015) showed DLDA outperforms DNN with CCE under the same network architecture, there is still some improvement potential in DLDA.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations